ANALISIS EKSPOR KAKAO INDONESIA DI PASAR INTERNASIONAL - Muhammad Ridho Al Ghozy; Aris Soelistiyo; Hendra Kusuma (Program Studi Ekonomi Pembangunan, 2017)
Cocoa is one of the main commodities that become the leading plantation sector to be marketed in international trade. The purpose of this research is to know the effect of cocoa production, world cocoa price and exchange rate to export. The data used is secondary data. The research method used is multiple linear regression analysis. This research method aims to determine the independent variables that affect the dependent variable. The result of the analysis shows that the three independent variables have significant effect simultaneously on the dependent variable. And the three independent variables have an effect on partially significant to the dependent variable. And it is expected that Indonesia's cocoa exports could be increased in the form of cocoa beans and other processed cocoa exports so that Indonesia's cocoa exports will increase.